Occurrence of metacercariae of Austrodiplostomum compactum (lutz, 1928) (trematoda, diplostomidae) in Pimelodus platicirris in the ilha solteira reservoir, São Paulo, Brazil - Campos, Denis W. J. [UNESP]; Manoel, Letícia O. [UNESP]; Franceschini, Lidiane [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP]; Delariva, Rosilene L.; Ribeiro, Cristiéle S. [UNESP]; Ramos, Igor Paiva [UNESP] (FapUNIFESP (SciELO), 2020)
This study reports the occurrence of metacercariae of Austrodiplostomum compactum in Pimelodus platicirris from a Neotropical reservoir in the Grande River, SP, Brazil. A total of 164 fish were collected, of which 12.80% were infected with metacercariae in the eyes. The mean intensity of infection and mean abundance were 1.52±0.14 (1-3) and 0.23±0.05 (0-3), respectively. The presence of this parasite with a high intensity of infection can cause exophthalmos, retinal displacement, opacity of the lens, blindness or even death. This is the fi rst record of ocular metacercariae for P. platicirris, thus increasing the number of hosts for A. compactum.
Keywords: Diplostomiasis; Freshwater fish; Mandi; Neotropical reservoir